Auf dem Weg zu einer Green Economy Wie die sozialökologische Transformation gelingen kann - Kahlenborn, Walter; Clausen, Jens; Behrendt, Siegfried; Göll, Edgar (Neue Ökologie, 2019)
Green economy is the future - this volume illuminates options, challenges and factors of success, providing perspectives for politics and the economy.